Physiological responses of cowpea (Vigna unguiculata L. Walp) varieties to Rhizobia inoculation, phosphorus application and sequential cropping system in Minna, Nigeria - Adediran, O.A. (Federal University of Technology Minna, 2019)
Cowpea is the most important grain legume in Nigeria but the yield obtained on farmers’ fields is far below the potential yield of the crop. This study aimed at exploiting rhizobia inoculation, phosphorus application, varietal differences and sequential cropping system to improve the productivity and profitability of cowpea per unit area in Minna, Nigeria. A glasshouse and two field experiments were conducted between 2015 and 2017. The glasshouse experiment was a factorial combination of four nitrogen sources (uninoculated, inoculated with USDA 3451 and USDA 3384 rhizobia strains and 90 kg N ha-1), soils collected from 20 locations in the Nigerian savannas and two varieties of cowpea (IT93K-452-1 and IT99K-573-1-1) replicated three times and laid in a completely randomized design. The first of the field experiments conducted on three farmers’ fields in Minna was a factorial combination of three nitrogen sources (uninoculated, inoculated with USDA 3451 and USDA 3384 rhizobia strains), three phosphorus rates (control, 20 kg P ha-1 and 40 kg P ha-1) and three varieties (IT93K-452-1, IT99K-573-1-1 and TVX-3236) in the first year. In the second and third year of planting, the strains were replaced with BR 3262 and BR 3267 and 90 kg N ha-1 was added as part of the treatments. The treatments were laid in randomized complete block design. The second field experiment evaluated the performance of six cowpea varieties (IT93K-452-1, IT99K-573-1-1, TVX-3236, Kanannado, Oloyin and IT90K-76) in cowpea sequential cropping system. Data were collected on growth, yield, nodulation and physiological parameters. The results revealed that the cowpea varieties successfully formed symbiosis with the introduced rhizobia strains in all the locations. Rhizobia inoculation increased nodulation in 11 out of the 20 locations with percentage increase ranging from 4 to 43%. Plants fertilized with 90 kg N ha-1 had significantly higher biomass yield than the inoculated and uninoculated plants which had similar biomass yield. Phosphorus significantly (P≤0.05) increased the photosynthetic activities, nodulation, N-fixation, growth and yield of the cowpea varieties in the three years with application of 20 kg P ha-1 increasing grain yield by 49-95% over the control. Significant interactions exists between rhizobia inoculation, phosphorus and varieties on some growth and yield attributes. IT99K-573-1-1 maintained the highest productivity among the varieties however, TVX-3236 appeared to be more P efficient having significantly higher growth rate, nodule weight and grain yield at lower P rates. Number of pods per plant had the highest correlation coefficient with grain yield in the three years (r=0.79). Crop growth rate (CGR), leaf area index (LAI) and quantum yield of photosystem II (Phi 2) explained 67.29% of the variation in grain yield (R2= 67.29%) and these three physiological parameters could significantly predict the grain yield. All the varieties were successfully planted in two sequence in each growing season except Kanannado and there was significant variation in the growth and yield attributes of the cowpea varieties in sequential cropping system. IT93K-452-1, IT99K-573-1-1, TVX-3236 and IT90K-76 all had significantly higher (P≤0.05) grain yield and profitability with gross margin ranging between ₦407,910 and ₦1,131, 967 than Oloyin and Kanannado varieties which had gross margin range of -₦123,065 and ₦88,931. Similarly, double cropping of these four varieties increased the gross margin by an average of 115% in 2016 and 140% in 2017 over the traditional system of planting once. It can be concluded from these results that N limits the productivity of cowpea in some soils of Nigerian savannas and rhizobia inoculation with highly effective strains than what was used in this study can overcome this limitation. CGR, LAI and Phi 2 could be exploited to increase the grain yield of cowpea through agronomic practices and plant breeding programs. Application of 20 kg P ha-1 is sufficient for the optimum performance of cowpea in the study area and double cropping of improved, early and medium maturing varieties of cowpea per season is capable of increasing the productivity and profitability of cowpea in the study area.